Anticipation : a novel - Winawer, Melodie (Gallery Books, 2021)
"From the author of the "engrossing historical epic" (Booklist) The Scribe of Siena comes a novel set in the crumbling city of Mystras, Greece, in which a scientist's vacation with her young son quickly turns into a fight for their lives after they cross paths with a man out of time"--